PENGARUH METODE PRAKTIKUM MENGGUNAKAN KIT OPTIK TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN CAHAYA DI KELAS VIII SMP NEGERI 1 PRABUMULIH - Indri Pratiwi (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This study aimed to determine the influence of practical method using optical KIT on learning outcomes of students on the subject of light in eighth grade SMPN 1 Prabumulih. This study uses a quasi-experimental with pretest-posttest control group design. Variabel this study is practical method using optical KIT and learning outcomes. The study population was all students of SMPN 1 Prabumulih school year 2012/2013, with a sample of class VIII F and VIII E totaling 69 students. Based on the results showeed information that the influence of practical method using optical KIT on learning outcomes of students on the subject of light in eighth grade SMPN 1 Prabumulih included in the criteria medium with the normalized gain score is 0.54. Based on the results of the t test from the value of student learning outcomes obtained tcalculate>ttable (2.196 > 1.996), thus Ho is rejected and Ha is accepted. This suggests that there are significant practical method using optical KIT on learning outcomes of students on the subject of light in eighth grade SMPN 1 Prabumulih.